Microstructures of as-Fabricated and Post Heat Treated Ti-47Al-2Nb-2Cr Alloy Produced by Selective Electron Beam Melting (SEBM). Issue 7 (July 2016) - Guangyu, Yang; Wenpeng, Jia; Pei, Zhao; Liang, Jia; Nan, Liu; Jian, Wang; Huiping, Tang
Abstract: The microstructures of as-fabricated and post heat treated Ti-47Al-2Nb-2Cr (at%) alloy produced by selective electron beam melting (SEBM) were examined. The solidification path and the phase transformation of Ti-47Al-2Nb-2Cr alloy during SEBM process were analyzed. Results show that the microstructure is fully lamellar (FL), consisting of fine γ -TiAl and α 2 -Ti3 Al, which is formed in the as-fabricated TiAl specimen. Due to the rapid cooling and the cyclic heat treatment during the SEBM process, the lamellar colonies and the lamellae width become coarser and wider, respectively from the top to the bottom of the specimen, solidification takes place solely through the β phase, and the phase transformation path is L → L + β → β → β + α → α → α + γ . Different post heat treatments were carried out to get a homogeneous microstructure. Results indicate that a fine and homogeneous microstructure can be achieved after oil quenching from 1250 °C and holding at 1200 °C for 2 h.